Positive Mental Health among University Students: The Role of Social Support and Self-Efficacy - Kholifah Umi Sholihah; Maulida Aulia Putri; Novia Ardha Maftuha; Zahrotul Izzah; Prapti Madyo Ratri (Manunggal Halim Jaya, 2026)
Student mental health has become an increasingly important issue because of the growing academic, social, and emotional demands experienced during university life. Positive mental health refers not only to the absence of psychological disorders but also to an individual's ability to function optimally in personal, academic, and social domains. Previous studies have identified social support and self-efficacy as important factors associated with mental well-being; however, research examining their simultaneous contributions to positive mental health among university students remains limited. This study aimed to examine the relationship between social support and self-efficacy and positive mental health among university students. A quantitative correlational design was employed, involving 103 university students selected through convenience sampling. Data were collected using the Positive Mental Health Scale, General Self-Efficacy Scale, and Social Support Scale, all of which demonstrated satisfactory reliability coefficients. Data were analyzed using multiple linear regression with the assistance of IBM SPSS Statistics (version 27). The results revealed that social support and self-efficacy simultaneously had a positive and significant relationship with positive mental health (R = 0.701, p < 0.001), contributing to 49.2% of the variance in positive mental health. Partial analyses further indicated that both social support and self-efficacy significantly predicted positive mental health outcomes. These findings suggest that strengthening social support systems and enhancing students’ self-efficacy may contribute to better mental health outcomes. Universities are encouraged to develop mental health promotion programs through counseling services, peer support initiatives, mentoring programs, and self-development training to enhance student well-being.